Anode active material, anode including anode active material, secondary battery including anode, and method for producing anode active material

A silicon-based negative electrode active material with controlled pores and carbon layers addresses the issues of irreversible phase formation and volume change, enhancing discharge capacity and battery life in lithium secondary batteries.

JP7657942B2Active Publication Date: 2025-04-07LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023544572
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-03
Filing Date
2022-07-27
Publication Date
2025-04-07
Estimated Expiration
2042-07-27

AI Technical Summary

Technical Problem

Existing silicon-based negative electrode active materials in lithium secondary batteries suffer from irreversible phase formation, reduced discharge capacity, and excessive volume change during charging and discharging, leading to reduced battery life due to side reactions with the electrolyte.

Method used

A negative electrode active material comprising silicon-based composite particles with controlled pores, an external carbon layer, and an internal carbon layer, manufactured through a process involving heat treatment and carbonaceous precursor application, to control pore size and improve conductivity.

Benefits of technology

The solution effectively reduces side reactions, enhances discharge capacity and initial efficiency, and improves battery life by suppressing volume change during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657942000005
    Figure 0007657942000005
  • Figure 0007657942000001
    Figure 0007657942000001
  • Figure 0007657942000002
    Figure 0007657942000002
Patent Text Reader

Abstract

The present invention relates to a silicon-based composite particle containing SiO x (0 < x < 2) and pores, and containing a Mg compound or a Li compound; an external carbon layer provided on the surface of the silicon-based composite particle; and an internal carbon layer provided inside the pores, with a BET specific surface area of 3 m 2 / g to 15 m 2 / g, a negative electrode active material containing the same, a negative electrode containing the same, a secondary battery containing the negative electrode, and a method for manufacturing the negative electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2021-0117633, filed with the Korean Intellectual Property Office on September 3, 2021, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a negative electrode active material, a negative electrode including the negative electrode active material, a secondary battery including the negative electrode, and a method for producing the negative electrode active material. [Background technology]

[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is the field of power generation and storage using electrochemical reactions.

[0004] At present, a representative example of such electrochemical elements that use electrochemical energy is a secondary battery, and the range of its use is expanding. In recent years, with the increase in technological development and demand for portable devices such as portable computers, mobile phones, and cameras, the demand for secondary batteries as energy sources has increased rapidly. Among these secondary batteries, much research has been conducted on high energy density, i.e., high capacity lithium secondary batteries, which have been commercialized and are widely used.

[0005] In general, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions that have come out of the positive electrode. Silicon-based particles having a large discharge capacity can be used as the negative electrode active material. However, SiO x The SiO2 in the silicon-based particles (0≦x<2) reacts partially with the lithium ions transferred from the positive electrode to generate lithium silicate, which acts as an irreversible phase and reduces the initial efficiency of the battery. In addition, the silicon-based particles change volume excessively during charging and discharging, causing side reactions with the electrolyte. This causes a problem of reduced battery life.

[0006] In the past, to solve this problem, a technology was used in which metals such as Mg were intentionally doped into silicon-based particles to block reaction sites that could form irreversible phases and improve initial efficiency. However, when this technology is applied, there is a drawback in that the discharge capacity per weight of the negative electrode active material is excessively reduced depending on the metal doping.

[0007] Therefore, a technique of removing a part of the metal compound due to the doped metal has been used, but this technique has a problem that a side reaction occurs between the negative electrode active material and the electrolyte due to the large pores, which reduces the life performance of the battery.

[0008] Meanwhile, a technique of forming a carbon layer is used to improve the conductivity of the negative electrode active material, but the general method of manufacturing the carbon layer has a problem in that the carbon layer is difficult to uniformly arrange on the surface and inside of the negative electrode active material, and therefore the improvement in the life performance of the battery is not significant.

[0009] Therefore, there is a need for an anode active material having small pores and a properly provided outer carbon layer and inner carbon layer, and a method for manufacturing the anode active material. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Korean Patent Publication No. 10-2019-0104895 Summary of the Invention [Problem to be solved by the invention]

[0011] One problem to be solved by the present invention is to provide a negative electrode active material capable of improving the initial efficiency and discharge capacity of a battery.

[0012] Another problem to be solved by the present invention is to provide a negative electrode containing the negative electrode active material.

[0013] Another problem to be solved by the present invention is to provide a secondary battery including the negative electrode.

[0014] Still another problem to be solved by the present invention is to provide a method for manufacturing the negative electrode active material.

Means for Solving the Problems

[0015] One embodiment of the present specification is SiO x (0 < x < 2) and pores, and silicon-based composite particles containing a Mg compound or a Li compound; an external carbon layer provided on the surface of the silicon-based composite particles; and an internal carbon layer provided inside the pores, and the BET specific surface area is 3 m 2 / g to 15 m 2 / g, and provides a negative electrode active material.

[0016] One embodiment of the present specification is SiO x (0 < x < 2), and a step of forming silicon-based composite particles containing pores from preliminary silicon-based composite particles containing a Mg compound or a Li compound; a step of arranging a carbonaceous precursor on the silicon-based composite particles and then performing a first heat treatment to form a preliminary negative electrode active material including an external carbon layer and an internal carbon layer; and a step of performing a second heat treatment on the preliminary negative electrode active material, and provides a method for manufacturing a negative electrode active material.

[0017] One embodiment of the present specification provides a negative electrode including the above-described negative electrode active material.

[0018] One embodiment of the present specification provides a secondary battery including the above-described negative electrode.

Effects of the Invention

[0019] The negative electrode active material according to one embodiment of the present invention can reduce the side reaction between the electrolyte and the negative electrode active material during the driving of the battery, and improve the life characteristics of the battery.

[0020] In addition, since the negative electrode active material contains silicon-based composite particles from which the metal compound and SiO2 have been at least partially removed, the discharge capacity and initial efficiency of the battery can be improved.

[0021] In addition, the external carbon layer formed on the surface of the silicon-based composite particle and the internal carbon layer formed inside the pores can easily suppress volume change of the negative active material during charging / discharging of the battery, thereby improving the life characteristics of the battery.

[0022] In addition, in the negative electrode active material according to one embodiment of the present invention, the pore size of the silicon-based composite particles before the carbon layer is formed during the manufacturing process is at a low level, so that the pore size can be easily controlled (the pore size is reduced and the number of pores is reduced) by heat treatment.

[0023] The negative electrode active material according to the present invention has a BET specific surface area of ​​3 m 2 / g~15m 2 / g, which is a lower value than the BET specific surface area of ​​metal-doped silicon-based particles including a general carbon layer. Conventional general particles have a large BET specific surface area because the pore size is not controlled, whereas the negative active material of the present invention has a low specific surface area by effectively controlling the size and number of pores, thereby reducing side reactions between the electrolyte and the negative active material during charging and discharging of the battery, thereby improving the life characteristics of the battery. [Brief description of the drawings]

[0024] [Figure 1] 1 shows a simplified structure of a negative electrode active material according to one embodiment of the present specification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] In the following, the present invention will be described in more detail to facilitate understanding of the present invention.

[0026] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0027] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. The singular expressions include the plural expressions unless otherwise clearly indicated in the context.

[0028] It should be understood that, as used herein, terms such as "comprises," "comprising," or "having" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.

[0029] In this specification, the pore size may refer to the average diameter of the pores contained in the negative electrode active material, that is, the size may indicate the average diameter of the pores.

[0030] In the present specification, the crystallinity of the structure contained in the negative active material may be confirmed by X-ray diffraction analysis, which may be performed using an XRD (X-ray diffraction) analysis device (product name: D4-endavor, manufacturer: Bruker), and other devices used in the industry may be appropriately adopted in addition to the above device. In one example, when a crystalline peak derived from a specific coating layer does not appear during X-ray diffraction analysis of the negative active material, the coating layer may be amorphous. Specifically, in the case of XRD, a crystalline peak is detected, and when there is no difference in the XRD graph of the negative active material before and after coating with a specific coating layer, it can be confirmed that the crystalline peak derived from the coating layer does not appear and the coating layer is an amorphous coating layer.

[0031] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the volume cumulative amount in the particle size distribution curve of the particles. The average particle size (D 50 ) can be measured, for example, using the laser diffraction method. The laser diffraction method can generally measure particle sizes in the range from the submicron region to about several millimeters, and can obtain results with high reproducibility and high resolution.

[0032] In this specification, the specific surface area can be measured by the BET 6-point method by removing gas (degassing) at 130 °C for 5 hours and performing N2 adsorption / desorption at 77 K using a BET measuring device (BEL-SORP-MAX, Nippon Bell) for the measurement target.

[0033] In the present invention, the pore size can be measured by a calculation formula according to the BJH (Barrett-Joyer-Halenda) method via the nitrogen adsorption method. Specifically, after deriving the pore area corresponding to the pore size using the BELSORP-mini II model of BEL Japan, the pore size showing the largest pore area was taken as representative. The BJH method can be used, and the plot of the measured values has the pore diameter (Dp / nm) on the X-axis and dVp / dDp (cm 3 g -1 nm -1 ) on the Y-axis.

[0034] <Negative electrode active material> The negative electrode active material according to one embodiment of this specification is a silicon-based composite particle containing SiO x (0 < x < 2) and pores, and containing a Mg compound or a Li compound; an external carbon layer provided on the surface of the silicon-based composite particle; and an internal carbon layer provided inside the pores, and the BET specific surface area is 3 m 2 / g to 15 m 2 / g.

[0035] As used herein, the provision of an external carbon layer on the surface of the silicon-based composite particles means that the carbon layer is located on the external surface of the silicon-based composite particles excluding pores. The external carbon layer may be in a form that partially covers at least a part of the surface of the silicon-based composite particles, i.e., covers the surface of the particles partially or covers the entire surface of the particles.

[0036] As used herein, the provision of an internal carbon layer inside the pores of the silicon-based composite particles means that the carbon layer is located on the surface and / or the internal space of the pores formed inside the silicon-based composite particles. The internal carbon layer may be in a form that partially covers at least a part of the pores contained in the silicon-based composite particles, i.e., covers the inside of the pores partially, covers the entire inside of the pores, or is provided inside the pores.

[0037] The presence of the external carbon layer and the internal carbon layer of the negative electrode active material can be confirmed by TEM or SEM. Specifically, the presence of the internal carbon layer can be confirmed by EDAX (Energy Dispersive Spectrometer) analysis of the SEM cross-section.

[0038] FIG. 1 schematically shows the structure of the negative electrode active material according to an embodiment of the present specification. The negative electrode active material according to an embodiment of the present specification includes an external carbon layer and an internal carbon layer. Specifically, the external carbon layer may exist in a form that covers the surface of the silicon-based composite particles, and the internal carbon layer may exist in a form that is located in the pores contained in the silicon-based composite particles.

[0039] The negative electrode active material according to an embodiment of the present specification includes silicon-based composite particles. The silicon-based composite particles include SiO x (0 < x < 2) and pores, and contain a Mg compound or a Li compound.

[0040] The silicon-based composite particles include SiO x (0 < x < 2), a Mg compound, and pores.

[0041] The aforesaid SiO x (0 < x < 2) corresponds to the matrix within the silicon-based composite particles. The aforesaid SiO x (0 < x < 2) may be in a form containing Si and SiO2, and the aforesaid Si may form a phase. That is, the aforesaid x corresponds to the number ratio of O to Si contained in the aforesaid SiO x (0 < x < 2). When the silicon-based composite particles contain the aforesaid SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0042] In one embodiment of the present specification, the aforesaid Mg compound may correspond to the matrix within the silicon-based composite particles.

[0043] The aforesaid Mg compound may be present inside and / or on the surface of the aforesaid SiO x (0 < x < 2). The aforesaid Mg compound can improve the initial efficiency of the battery.

[0044] The aforesaid Mg compound may contain at least any one selected from the group consisting of Mg silicate, Mg silicide, and Mg oxide. The aforesaid Mg silicate may contain at least any one of Mg2SiO4 and MgSiO3. The aforesaid Mg silicide may contain Mg2Si. The aforesaid Mg oxide may contain MgO.

[0045] In one embodiment of the present specification, the aforesaid Mg element is contained at 0.1 wt% to 20 wt% based on the total 100 wt% of the negative electrode active material, or may be contained at 0.1 wt% to 10 wt%. Specifically, the aforesaid Mg element may be contained at 0.5 wt% to 8 wt%, or 0.8 wt% to 4 wt%. When the aforesaid range is satisfied, since the Mg compound is contained in an appropriate content in the negative electrode active material, the volume change of the negative electrode active material during charging and discharging of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0046] The silicon-based composite particles contain SiO x (0 < x < 2), a Li compound, and pores.

[0047] In one embodiment of the present specification, the Li compound may correspond to a matrix within the silicon-based composite particles.

[0048] In one embodiment of the present specification, the Li compound may be present inside and / or on the surface of the SiO x (0 < x < 2). The initial efficiency of the battery can be improved by the Li compound.

[0049] The Li compound may include at least any one selected from the group consisting of Li silicate, Li silicide, and Li oxide. The Li silicate may include at least any one of Li2SiO3, Li4SiO4, and Li2Si2O5. The Li silicide may include Li7Si2. The Li oxide may include Li2O.

[0050] In one embodiment of the present invention, the Li compound may include a form of lithium silicate. The lithium silicate is represented by Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be classified into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may be present in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5 within the silicon-based composite particles, and the amorphous lithium silicate may be in the form of Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and is not limited to the above form.

[0051] In one embodiment of the present specification, the Li element may be included in an amount of 0.1 wt% to 20 wt% or 0.1 wt% to 10 wt% based on the total weight of the negative electrode active material (100 wt%). Specifically, the Li element may be included in an amount of 0.5 wt% to 8 wt%, more specifically, 0.5 wt% to 4 wt%. When the above range is satisfied, the Li compound is included in the negative electrode active material in an appropriate content, so that the volume change of the negative electrode active material during charging and discharging of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0052] The content of the Mg element or Li element can be confirmed by ICP analysis. For the ICP analysis, a certain amount (about 0.01 g) of the negative active material is accurately taken and then transferred to a platinum crucible, and nitric acid, hydrofluoric acid, and sulfuric acid are added to completely decompose the negative active material on a hot plate. Then, an inductively coupled plasma emission spectrometry (ICPAES, Perkin-Elmer 7300) is used to measure the intensity of a standard solution prepared using a standard solution (5 mg / kg) at the characteristic wavelength of the Mg element or Li element to create a reference calibration curve. Then, the pretreated sample solution and a blank sample are introduced into the instrument, and the respective intensities are measured to calculate the actual intensities, and the concentrations of each component are calculated by comparing them with the created calibration curve, and the total sum is converted to a theoretical value, so that the Mg element or Li element content of the negative active material produced can be analyzed.

[0053] In one embodiment of the present specification, the silicon-based composite particles have a BET specific surface area of ​​3 m 2 / g~80m 2 / g, specifically 10m 2 / g~60m 2 / g, more specifically 15m 2 / g~50m 2 The silicon-based composite particles may have a BET specific surface area of ​​3 m 2 When the BET specific surface area of ​​the silicon-based composite particles is less than 80 m / g, the volume change of the negative electrode active material during charging and discharging cannot be effectively suppressed, and the battery life characteristics may be deteriorated. 2If it exceeds 1 / g, side reactions between the electrolyte and the negative electrode active material increase, and the life characteristics of the battery may deteriorate.

[0054] In one embodiment of the present specification, the silicon-based composite particles have an outer carbon layer on the surface thereof, and an inner carbon layer inside the pores of the silicon-based composite particles. The carbon layers formed on the surface and inside the pores of the silicon-based composite particles as described above impart electrical conductivity to the silicon-based composite particles, and can improve the initial efficiency, life characteristics, and capacity characteristics of a secondary battery that includes a negative electrode active material that includes the silicon-based composite particles.

[0055] In one embodiment of the present specification, the outer carbon layer or the inner carbon layer may include at least one of amorphous carbon and crystalline carbon.

[0056] The crystalline carbon may further improve the electrical conductivity of the silicon-based composite particles. The crystalline carbon may include at least one selected from the group consisting of fullerene, carbon nanotube, and graphene.

[0057] The amorphous carbon can appropriately maintain the strength of the carbon layer and suppress the expansion of the silicon-based composite particles. The amorphous carbon may be a carbon-based material formed by using at least one carbide selected from the group consisting of tar, pitch, and other organic substances, or a hydrocarbon as a source of a chemical vapor deposition process.

[0058] The other carbonized organic matter may be a carbonized organic matter selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose, or ketohexose, and combinations thereof.

[0059] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic or alicyclic hydrocarbon of the substituted or unsubstituted aliphatic or alicyclic hydrocarbon may be methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, or hexane, etc. The aromatic hydrocarbon of the substituted or unsubstituted aromatic hydrocarbon may be benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, or phenanthrene, etc.

[0060] In one embodiment of the present specification, the total weight of the external carbon layer and the internal carbon layer may be 5 wt% to 40 wt% based on 100 wt% of the total of the negative electrode active material. Specifically, it may be 5 wt% to 37 wt%, 10 wt% to 37 wt%, or 20 wt% to 37 wt%. When the range is satisfied, the conductivity of the negative electrode active material is improved, and the volume change of the negative electrode active material during charging and discharging of the battery is easily suppressed, and the life characteristics of the battery can be improved. The lower limit of the total weight of the carbon layer may be 5 wt%, 10 wt%, 15 wt%, or 20 wt%, and the upper limit may be 40 wt%, 38 wt%, 37 wt%, or 36 wt%.

[0061] In one embodiment of the present specification, the outer carbon layer may be included in an amount of 1 wt% to 10 wt% based on the total weight of the negative active material (100 wt%), specifically, 2 wt% to 9 wt%, and more specifically, 2 wt% to 8 wt%. When the above range is satisfied, the volume change of the negative active material during charging and discharging of the battery can be effectively suppressed. The lower limit of the content of the outer carbon layer may be 1 wt%, 2 wt%, or 2.5 wt%, and the upper limit may be 10 wt%, 9 wt%, 8 wt%, 7 wt%, or 6 wt%.

[0062] In one embodiment of the present specification, the inner carbon layer may be included in an amount of 4 wt% to 35 wt%, 4 wt% to 34 wt%, or 10 wt% to 34 wt% based on the total 100 wt% of the negative electrode active material. Specifically, the inner carbon layer may be included in an amount of 8 wt% to 30 wt%, and more specifically, 10 wt% to 30 wt%. When the inner carbon layer content satisfies the above range, the conductivity of the negative electrode active material is improved, and the life characteristics of the battery can be improved. The lower limit of the content of the inner carbon layer may be 4 wt%, 6 wt%, 8 wt%, 10 wt%, 12 wt%, 14 wt%, 16 wt%, 18 wt%, 20 wt%, or 21 wt%, and the upper limit may be 35 wt%, 34 wt%, 33 wt%, 32 wt%, 31 wt%, or 30 wt%.

[0063] The total carbon content of the negative active material can be measured by burning a sample together with a combustion improver in an oxygen stream using a CS analyzer.

[0064] The content of the outer carbon layer of the negative active material may be determined by calculation using the size of the negative active material particles, the thickness of the outer carbon layer, and the true density of the carbon layer, and the content of the inner carbon layer may be determined by calculation as the difference between the content of the entire carbon layer and the content of the outer carbon layer.

[0065] Specifically, since the circularity of the silicon-based composite particles is 0.9 or more, the calculation is performed assuming that the silicon-based particles are spherical. The diameter of the silicon-based composite particles before the carbon layer is formed can be measured using a particle size analyzer, and the thickness of the outer carbon layer provided on the silicon-based composite particles after the carbon layer is formed can be measured using a TEM, and the volumes of the silicon-based composite particles and the outer carbon layer can be calculated from the measured values, and the masses and the content of the outer carbon layer can be calculated by multiplying the true densities of the silicon-based composite particles and the carbon layer. The true density can be measured using a pycnometer (AccuPyc 1340, Micromeritics Instrument Corp. USZ).

[0066] In one embodiment of the present specification, the thickness of the outer carbon layer may be 1 nm to 500 nm, specifically, 5 nm to 300 nm, 10 nm to 100 nm, or 25 nm to 50 nm. When the thickness satisfies the above range, the volume change of the negative electrode active material is easily suppressed, and a side reaction between the electrolyte and the negative electrode active material is suppressed, thereby improving the life characteristics of the battery.

[0067] The thickness of the outer carbon layer can be measured using a TEM and can refer to the average value of the measured thickness.

[0068] In one embodiment of the present specification, the BET specific surface area of ​​the negative electrode active material is 3 m 2 / g~15m 2 / g, specifically 5m 2 / g~15m 2 / g, more specifically 8m 2 / g~14m 2 When the above range is satisfied, the side reaction between the electrolyte and the negative active material during charging and discharging of the battery can be reduced, thereby improving the life characteristics of the battery. The lower limit of the BET specific surface area is 3 m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, or 8m 2 / g, with an upper limit of 15m 2 / g, 14m 2 / g, 13m 2 / g, 12m 2 / g, 11m 2 / g, or 10m 2 / g.

[0069] The BET specific surface area is generally lower than the BET specific surface area of ​​metal-doped silicon-based particles containing a carbon layer. In the case of conventional general particles, a carbon layer is formed on silicon-based composite particles with uncontrolled pore size, but in the case of silicon-based composite particles with uncontrolled pore size, the pore size does not easily decrease even when heat is applied. Therefore, in the case of conventional general particles, the BET specific surface area is inevitably large. In contrast, in the present invention, the silicon-based composite particles with a low pore size are used, and an additional heat treatment is performed after the formation of the carbon layer, so that the size and number of pores can be effectively controlled, and the BET specific surface area can be increased to 3 m. 2 / g~15m 2 A low specific surface area of ​​0.1 g / g can be derived.

[0070] In this specification, the size of the pores in the negative active material refers to the size excluding the inner carbon layer provided in the pores, that is, the size of the pores before the carbon layer is formed.

[0071] In one embodiment of the present specification, the size of the pores may be 50 nm or less, specifically, 1 nm to 40 nm, or 2 nm to 35 nm. In another embodiment, the size of the pores may be 5 nm to 35 nm, 10 nm to 35 nm, or 10 to 30 nm.

[0072] In one embodiment herein, the lower limit of the pore size may be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, or 10 nm, and the upper limit may be 50 nm, 45 nm, 40 nm, 35 nm, 30 nm, 25 nm, or 20 nm.

[0073] When the size of the pores exceeds 50 nm, the side reaction between the electrolyte and the silicon-based composite particles increases, and the life characteristics of the battery deteriorate. Also, even if additional heat treatment is performed, the size and number of the pores cannot be controlled. The size of the pores is specially controlled by processes such as synthesis, etching, and additional heat treatment of the silicon-based composite particles, and corresponds to a lower value compared to the pore size of conventional silicon-based composite particles.

[0074] When the size of the pores is less than 2 nm, it is difficult for the pores to accept an excessive change in the volume of the silicon-based composite particles, and the degree of volume change of the battery becomes severe, thereby deteriorating the life characteristics of the battery. The size of the pores is specially controlled by processes such as synthesis, etching, and additional heat treatment of the silicon-based composite particles, and corresponds to a lower value compared to the pore size of conventional silicon-based composite particles.

[0075] The average particle size (D 50 ) of the negative electrode active material may be 2 μm to 15 μm, specifically may be 3 μm to 12 μm, and more specifically may be 4 μm to 10 μm. When the above range is satisfied, the side reaction between the negative electrode active material and the electrolyte is controlled, and the discharge capacity and initial efficiency of the battery can be effectively realized.

[0076] <Method for manufacturing negative electrode active material> The method for manufacturing a negative electrode active material according to an embodiment of the present specification includes a step of forming silicon-based composite particles containing pores from preliminary silicon-based composite particles containing SiO x (0 < x < 2) and containing a Mg compound or a Li compound; a step of performing a first heat treatment after disposing a carbonaceous precursor on the silicon-based composite particles to form a preliminary negative electrode active material including an external carbon layer and an internal carbon layer; and a step of performing a second heat treatment on the preliminary negative electrode active material.

[0077] Regarding the negative electrode active material, the content related to the negative electrode active material described above can be applied.

[0078] According to one embodiment of the present specification, a method for manufacturing a negative electrode active material includes SiO x forming silicon-based composite particles containing pores from preliminary silicon-based composite particles containing SiO x (0 < x < 2) and a Mg compound or a Li compound; placing a carbonaceous precursor on the silicon-based composite particles and then performing a first heat treatment to form a preliminary negative electrode active material containing an external carbon layer and an internal carbon layer; and performing a second heat treatment on the preliminary negative electrode active material.

[0079] The preliminary silicon-based composite particles are silicon-based oxide particles containing SiO x (0 < x < 2), and the silicon-based oxide particles contain one or more of a Mg compound and a Li compound. The Mg compound or Li compound may be distributed on the surface and / or inside of the silicon-based particles in a doped form. x

[0080] In one embodiment of the present specification, the preliminary silicon-based composite particles may be formed by vaporizing Si powder and SiO2 powder and then mixing them with Li or Mg respectively to form a mixed gas; and heat-treating the mixed gas.

[0081] In one embodiment of the present specification, the preliminary silicon-based composite particles may be formed by vaporizing Si powder and SiO2 powder and then mixing them with Mg respectively to form a mixed gas; and heat-treating the mixed gas at 800°C to 950°C in a vacuum state. Further, additional heat treatment may be performed after the heat treatment, and the additional heat treatment may be performed at 800°C to 1000°C.

[0082] The mixed powder of the Si powder and the SiO2 powder may be heat-treated and vaporized at 1000°C to 1800°C or 1200°C to 1500°C, and the Mg powder may be heat-treated and vaporized at 500°C to 1200°C or 600°C to 800°C.

[0083] The step of heat-treating the mixed gas in a vacuum at 800°C to 950°C may include a step of heat-treating the mixed gas at 800°C to 900°C for 30 minutes to 1 hour and 30 minutes, and then additionally heat-treating the mixed gas at 850°C to 900°C for 2 hours to 4 hours.

[0084] The step of heat-treating the mixed gas may be performed at a constant temperature, thereby forming small pores in the preliminary silicon-based particles, and thus forming small pores in the silicon-based composite particles during subsequent etching.

[0085] In the preliminary silicon-based composite particles, the Mg compound may include the above-mentioned Mg silicate, Mg silicide, Mg oxide, etc.

[0086] In one embodiment of the present specification, the preliminary silicon-based composite particles may be formed by the steps of: vaporizing a mixture of Si powder and SiO2 powder and Li, and then mixing them to form a mixed gas; and heat-treating the mixed gas in a vacuum at 800° C. to 950° C. In addition, an additional heat treatment may be performed after the heat treatment, and the additional heat treatment may be performed at 800° C. to 1000° C.

[0087] In another embodiment, the preliminary silicon-based composite particles may be formed by the steps of: forming silicon-based oxide particles; and distributing a Li compound into the formed silicon-based oxide particles.

[0088] The silicon-based oxide particles may be formed by heat-treating a powder mixture of Si powder and SiO2 powder. Specifically, the method may include a step of heating and vaporizing the mixed powder of Si powder and SiO2 powder in a vacuum, and then depositing the vaporized mixed gas.

[0089] The mixed powder of the Si powder and the SiO2 powder may be heat-treated at 1000°C to 1800°C or 1200°C to 1500°C to be vaporized.

[0090] The preliminary silicon-based composite particles may be silicon-based oxide particles containing SiO x (0 < x < 2).

[0091] The step of distributing the Li compound in the formed silicon-based oxide particles includes the step of mixing the silicon-based oxide particles and the Li precursor. If necessary, the step may be performed under heat treatment or by using an electrochemical method.

[0092] The Li precursor may be, for example, but not limited to, Li powder, LiOH, Li2O, etc. It may be performed by mixing and, if necessary, heat treating at 400°C to 1400°C.

[0093] The step of heat treating after mixing the formed silicon-based oxide and the Li precursor may be performed in an inert atmosphere.

[0094] The step of heat treating after mixing the formed silicon-based oxide and the Li precursor may be performed in an inert atmosphere at 400°C to 1400°C, 500°C to 1000°C, or 700°C to 900°C. Further, additional heat treatment may be performed after the heat treatment, and the additional heat treatment may be performed at 700°C to 1100°C or 800°C to 1000°C.

[0095] In the preliminary silicon-based negative electrode active material, the Li compound phase may include the aforementioned Li silicate, Li silicide, Li oxide, etc.

[0096] Further, it may further include the step of forming a carbon layer before distributing the Li compound in the silicon-based oxide particles.

[0097] The step of forming the carbon layer may be performed by chemical vapor deposition (CVD), specifically, by using at least one hydrocarbon gas selected from the group consisting of methane, ethane, and acetylene. More specifically, the step of forming the carbon layer may be performed by providing at least one hydrocarbon gas selected from the group consisting of methane, ethane, and acetylene to the acid-treated composition for forming a negative active material, followed by heat treatment by chemical vapor deposition (CVD). By this method, a carbon layer can be formed on silicon-based oxide particles at a uniform level, so that the volume expansion of the particles can be smoothly controlled and side reactions caused by the electrolyte can be prevented.

[0098] The carbon layer forming step may be performed at 800° C. to 1100° C., preferably 850° C. to 1000° C., in order to prevent any change in the crystalline phase and the amorphous phase in the negative electrode active material produced in the step.

[0099] In one embodiment of the present invention, the method for producing the negative electrode active material may include a step of forming a surface layer on at least a part of a surface of the negative electrode active material. The surface layer may include at least one selected from the group consisting of aluminum phosphate and lithium phosphate. The surface layer may include aluminum phosphate and lithium phosphate.

[0100] In one embodiment of the present specification, the step of forming silicon-based composite particles including pores from the preliminary silicon-based composite particles may include a step of etching the preliminary silicon-based particles using an acid or a base. In this case, the acid may be at least one of hydrofluoric acid (HF), nitric acid (HNO3), sulfuric acid (H2SO4), and hydrochloric acid (HCl), and the base may be at least one of sodium hydroxide (NaOH) and potassium hydroxide (KOH). Specifically, a mixed solution of hydrofluoric acid and ethanol may be used during the etching. The Mg compound or Li compound and SiO2 of the preliminary silicon-based particles are removed by the etching step, so that the discharge capacity and efficiency of the battery can be improved. The etching may be performed for 1 hour to 3 hours.

[0101] At this time, the pores of the formed silicon-based composite particles can be formed to be small in size.

[0102] In the case of pores that do not satisfy the above range, the pore size is large, so the pore size does not change significantly even after the first and second heat treatments, but in the case of pores that satisfy the above range, the pore size is small, so the pore size can be easily controlled by the first and second heat treatments. Therefore, the size of the pores arranged in the silicon-based composite particles can be further easily reduced by performing a first heat treatment on the silicon-based composite particles containing the pores to form a preliminary negative electrode active material containing a carbon layer; and a second heat treatment on the preliminary negative electrode active material.

[0103] In one embodiment of the present specification, the step of forming the preliminary negative electrode active material may include a process of disposing a carbonaceous precursor on silicon-based composite particles and then performing a first heat treatment.

[0104] In one embodiment of the present specification, the step of forming the preliminary negative active material may include disposing a carbonaceous precursor on the silicon-based composite particles and then performing a first heat treatment. The carbonaceous precursor may be graphene or graphite for producing crystalline carbon, or may be a carbonaceous material formed by using at least one carbide or hydrocarbon selected from the group consisting of tar, pitch, and other organic substances as a source for chemical vapor deposition for producing amorphous carbon.

[0105] The carbon layer formed by the first heat treatment of the carbonaceous precursor may comprise crystalline or amorphous carbon.

[0106] Specifically, the carbon layer containing crystalline carbon may be formed by mixing inorganic particles or inorganic oxide particles and crystalline carbon in a solid or liquid phase, followed by heat treatment.The carbon layer containing amorphous carbon may be formed by coating the surfaces of inorganic particles or inorganic oxide particles with an amorphous carbon precursor, followed by heat treatment for carbonization.

[0107] Representative examples of the crystalline carbon include graphene and graphite. Representative examples of the amorphous carbon precursor include resins such as phenol resin, naphthalene resin, polyvinyl alcohol resin, urethane resin, polyimide resin, furan resin, cellulose resin, epoxy resin, and polystyrene resin, coal-based pitch, tar, and low molecular weight heavy oil.

[0108] The first heat treatment may be performed at 600°C to 1100°C or 600°C to 1000°C, specifically 700°C to 1000°C, more specifically 800°C to 970°C. When the above range is satisfied, a carbon layer having a suitable crystal structure can be easily formed on the surface of the negative electrode active material. The first heat treatment time may be 1 hour to 5 hours, specifically 3 hours to 5 hours.

[0109] A method for producing a negative electrode active material according to one embodiment of the present specification includes a step of subjecting the preliminary negative electrode active material to a second heat treatment.

[0110] By heat treating the preliminary negative active material having the outer carbon layer and the inner carbon layer formed thereon, the size and number of pores present in the preliminary negative active material can be reduced, thereby reducing side reactions between the negative active material and an electrolyte and improving the life characteristics of the battery.

[0111] The second heat treatment may be performed at 600° C. to 1100° C., specifically, 900° C. to 1050° C. When the temperature is within this range, the size and number of pores in the silicon-based composite particles can be effectively reduced, thereby reducing side reactions between the negative electrode active material and the electrolyte, and improving the life characteristics of the battery.

[0112] The second heat treatment time may be from 1 hour to 5 hours, specifically from 3 hours to 4 hours.

[0113] The size of the pores formed by the second heat treatment may be 50 nm or less, specifically, 1 nm to 40 nm, or 2 nm to 35 nm. In another embodiment, the size of the pores may be 5 nm to 35 nm, 10 nm to 35 nm, or 10 to 30 nm.

[0114] <Negative electrode> A negative electrode according to an embodiment of the present specification may include a negative electrode active material, where the negative electrode active material is the same as the negative electrode active material of the above-mentioned embodiment. Specifically, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include the negative electrode active material. Furthermore, the negative electrode active material layer may further include a binder and / or a conductive material.

[0115] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has electrical conductivity. For example, the current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like. Specifically, a transition metal that easily adsorbs carbon, such as copper or nickel, may be used as the current collector. The thickness of the current collector may be 6 μm to 20 μm, but is not limited thereto.

[0116] The binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen of these is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.

[0117] The conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0118] <Secondary battery> A secondary battery according to an embodiment of the present specification may include the negative electrode of the above-mentioned embodiment. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.

[0119] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.

[0120] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0121] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be lithium metal (Li-metal).

[0122] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material described above.

[0123] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause chemical changes in the battery that is constructed and has electronic conductivity.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one of these may be used alone or a mixture of two or more of them may be used.

[0124] In addition, the positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector.Specific examples of the positive electrode binder include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.

[0125] The separator is a separator that separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is normally used as a separator in a secondary battery can be used without any particular restrictions, and it is particularly preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte moisture absorption ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.

[0126] Examples of the electrolytic solution include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries.

[0127] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0128] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0129] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, can be preferably used since they have a high dielectric constant as a high-viscosity organic solvent and dissociate lithium salts well. When such a cyclic carbonate is mixed with a linear carbonate having a low viscosity and a low dielectric constant, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte solution having high electrical conductivity can be prepared, and therefore such a mixture can be used more preferably.

[0130] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte solution. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.

[0131] In addition to the components of the electrolyte, the electrolyte may further include one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0132] According to an embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and therefore can be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system.

[0133] <Example> Below, preferred embodiments are presented to aid in understanding the present invention. However, the above embodiments are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present description. It goes without saying that such changes and modifications fall within the scope of the appended claims.

[0134] <Example 1> (Example 1-1) (1) Preparation of preliminary silicon-based composite particles 200g of powder obtained by uniformly mixing Si powder and SiO2 powder at a molar ratio of 1:1 and 10g of Mg were heat-treated at 1400°C and 700°C, respectively, in a reduced pressure atmosphere to vaporize the Si powder, the SiO2 powder, and the Mg. The mixed gas of the vaporized Si powder, the SiO2 powder, and the Mg was heat-treated in a vacuum chamber at 800°C for 1 hour, and then additionally heat-treated at a temperature of 900°C for 3 hours to produce particles. The particles were pulverized with a jet mill to form preliminary silicon-based composite particles.

[0135] (2) Formation of silicon-based composite particles A mixed solution of hydrofluoric acid and ethanol was used as the etching solution. The preliminary silicon-based composite particles were added to the etching solution in a weight ratio of 20:1, mixed for about 1 hour and 30 minutes, and then filtered, washed, and dried to form silicon-based composite particles. The average particle size (D 50 ) was 5 μm and the pore size was 20 nm.

[0136] (3) Preparation of reserve negative electrode active material The silicon-based composite particles were placed in a hot zone of a CVD apparatus while maintaining an inert atmosphere by flowing Ar gas around the silicon-based composite particles. The methane was then blown into the hot zone at 920° C. using Ar as a carrier gas for 3 hours and 10 minutes. -1 The reaction was carried out at torr to form a preliminary negative electrode active material having an outer carbon layer (thickness: 30 nm) formed on the surface of the silicon-based composite particles and an inner carbon layer formed inside the pores.

[0137] (4) Manufacture of negative electrode active material The preliminary negative active material having the outer and inner carbon layers was subjected to an additional heat treatment (second heat treatment) at 950° C. for 3 hours to control the size and number of pores in the silicon-based composite particles, thereby producing a negative active material. 50 ) is 5 μm, and the BET specific surface area is approximately 8.1 m 2 / g and the pore size was 15 nm.

[0138] The negative active material had a magnesium content of 3.5 wt%, and the total weight of the outer carbon layer and the inner carbon layer was 25 wt% based on 100 wt% of the negative active material. Specifically, the outer carbon layer was 3.5 wt% and the inner carbon layer was 21.5 wt% based on 100 wt% of the negative active material.

[0139] (Example 1-2) A negative active material was prepared in the same manner as in Example 1-1, except that the preliminary silicon-based composite particles were mixed in the etching solution for 2 hours.

[0140] (Examples 1-3) A negative electrode active material was prepared in the same manner as in Example 1-1, except that the silicon-based composite particles were reacted with methane in a hot zone at 920° C. for 5 hours.

[0141] (Examples 1 to 4) A negative electrode active material was prepared in the same manner as in Example 1-1, except that the preliminary silicon-based composite particles were mixed in the etching solution for 3 hours, and then reacted with methane in a hot zone at 920° C. for 4 hours.

[0142] (Comparative Example 1-1) A negative electrode active material was prepared in the same manner as in Example 1-1, except that the preliminary silicon-based composite particles were not etched.

[0143] (Comparative Example 1-2) A negative electrode active material was prepared in the same manner as in Example 1-1, except that the preliminary silicon-based composite particles were mixed in the etching solution for 6 hours, and then reacted with methane in a hot zone at 920° C. for 1 hour.

[0144] (Comparative Example 1-3) A negative electrode active material was prepared in the same manner as in Example 1-1, except that the silicon-based composite particles were reacted with methane in a hot zone at 970° C. for 5 hours.

[0145] [Table 1]

[0146] The specific surface areas of the silicon-based composite particles and the negative electrode active material were measured by the BET (Brunauer-Emmett-Teller; BET) method. Specifically, the specific surface areas were measured by the BET 6-point method using a porosimetry analyzer (Belsorp-II mini, Bell Japan Inc.) and a nitrogen gas adsorption flow method.

[0147] The pore size was measured by a formula based on the BJH (Barrett-Joyer-Halenda) method via nitrogen adsorption. Specifically, the pore area according to the pore size was calculated using the BELSORP-mini II model from BEL Japan, and the pore size (Dp / nm) showing the largest pore area (dVp / dDp) was then measured.

[0148] The Mg element content was measured by ICP analysis. Specifically, a certain amount (about 0.01 g) of the negative active material was taken and transferred to a platinum crucible, and nitric acid, hydrofluoric acid, and sulfuric acid were added to completely decompose the negative active material on a hot plate. Then, an inductively coupled plasma emission spectrometry (ICPAES, Perkin-Elmer 7300) was used to measure the intensity of a standard solution prepared using a standard solution (5 mg / kg) at the characteristic wavelength of Mg element to create a reference calibration curve. Then, the pretreated sample solution and a blank sample were introduced into the instrument, and the intensity of each was measured to calculate the actual intensity. The concentration of each component was calculated by comparing it with the created calibration curve, and the total sum was converted to a theoretical value, and the Mg element content of the negative active material was analyzed.

[0149] The average particle size of the silicon-based particles (D 50 ) can be defined as the particle size at 50% of the particle size distribution. The average particle size was measured using a laser diffraction method.

[0150] The internal carbon layer of the negative electrode active material was confirmed by EDAX (Energy Dispersive Spectrometer) analysis of the SEM cross section.

[0151] The thickness of the outer carbon layer of the negative electrode active material was measured via TEM.

[0152] The total carbon content of the negative active material was measured by burning the sample together with a combustion improver in an oxygen stream using a CS analyzer.

[0153] The content of the outer carbon layer of the negative active material was confirmed by calculation using the size of the negative active material particle, the thickness of the outer carbon layer, and the true density of the carbon layer, and the content of the inner carbon layer was confirmed by calculation as the difference between the content of the entire carbon layer and the content of the outer carbon layer. Specifically, the diameter of the silicon-based composite particle before the carbon layer was formed was measured using a particle size analyzer, and the thickness of the outer carbon layer provided on the silicon-based composite particle after the carbon layer was formed was measured using a TEM, and the volumes of the silicon-based composite particle and the negative active material were calculated from the results, and the respective masses and the content of the outer carbon layer were calculated by multiplying them by the true density. The true density was measured using a pycnometer (AccuPyc 1340, Micromeritics Instrument Corp. USZ).

[0154] <Experimental Example 1: Evaluation of discharge capacity, initial efficiency, and life (capacity retention rate) characteristics> Negative electrodes and batteries were manufactured using the negative electrode active materials of the examples and comparative examples, respectively.

[0155] The negative electrode active material and natural graphite were mixed in a weight ratio of 1:9 to prepare a mixed negative electrode active material, carbon black as a conductive material, and carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) as binders in a weight ratio of mixed negative electrode active material:conductive material:binder (CMC):binder (styrene butadiene) = 95.4:1:1.1:2.5, together with water as a solvent to prepare a negative electrode slurry (solid content was about 47% by weight based on the total weight of the negative electrode slurry).The negative electrode slurry was applied to a copper (Cu) metal thin film as a negative electrode current collector, dried, and punched to a certain size to prepare a negative electrode.

[0156] Li metal was used as the counter electrode. A polyolefin separator was placed between the negative electrode and Li metal, and an electrolyte solution in which 1M LiPF6 was dissolved in a solvent made by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7 was injected to fabricate a lithium coin-type half cell.

[0157] The produced batteries were charged and discharged to evaluate the discharge capacity, initial efficiency, and capacity retention rate. The results are shown in Table 2 below.

[0158] The first and second cycles were charged and discharged at 0.1 C, and the third to 49th cycles were charged and discharged at 0.5 C. The 50th cycle was completed in a charged state (with lithium in the negative electrode).

[0159] Charging conditions: CC (constant current) / CV (constant voltage) (5mV / 0.005C current cut-off) Discharge conditions: CC (constant current) conditions 1.5V voltage cut-off

[0160] From the results of one charge and discharge, the discharge capacity (mAh / g) and initial efficiency (%) were derived. Specifically, the charge / discharge capacity and initial efficiency were calculated by inversely converting the discharge capacity and initial efficiency of graphite alone, which were 365mAh / g and 93%, respectively, to calculate the discharge capacity and initial efficiency of the negative electrode active material of the present invention alone. Discharge capacity of negative electrode active material (mAh / g) = (measured discharge capacity - (0.9 x 365)) x 10 Charge capacity of negative electrode active material (mAh / g) = (measured charge capacity - (0.9 x 365 / 0.93)) x 10 Initial efficiency (%) = (discharge capacity of negative electrode active material (mAh / g) / charge capacity of negative electrode active material (mAh / g)) × 100

[0161] The capacity retention rate was calculated as follows. Capacity retention rate (%) = (49 discharge capacity / 1 discharge capacity) × 100

[0162] [Table 2]

[0163] The negative electrode active material according to the present invention is characterized in that it contains pores in silicon-based composite particles, an internal carbon layer in the pores, and an external carbon layer on the surface of the silicon-based composite particles, and the volume change of the negative electrode active material during charging and discharging of the battery is easily suppressed, the conductivity of the negative electrode active material is improved, and the life characteristics of the battery can be improved. Therefore, it can be confirmed that Examples 1-1 to 1-4 using the negative electrode active material according to the present invention show excellent discharge capacity, initial efficiency, and capacity retention rate.

[0164] In contrast, the negative active material used in Comparative Example 1-1 has a small BET specific surface area, and is unable to effectively suppress the volume change of the negative active material during charging and discharging, which deteriorates the battery life characteristics. Also, the negative active materials used in Comparative Examples 1-2 and 1-3 have an excessively large BET specific surface area due to an excessively large pore size or an inadequate carbon layer, which increases side reactions between the electrolyte and the negative active material, which deteriorates the battery life characteristics.

[0165] <Example 2> (Example 2-1) (1) Preparation of preliminary silicon-based composite particles A powder obtained by uniformly mixing Si powder and SiO2 powder in a 1:1 molar ratio was heat-treated at 1400°C in a reduced pressure atmosphere to recover SiO powder. The recovered SiO powder and Li metal powder were heat-treated in an inert atmosphere at 800°C for 1 hour, and then additionally heat-treated at 900°C for 3 hours to produce particles. The particles were pulverized in a jet mill to form preliminary silicon-based composite particles.

[0166] (2) Formation of silicon-based composite particles A mixed solution of hydrofluoric acid and ethanol was used as the etching solution. The preliminary silicon-based composite particles were added to the etching solution in a weight ratio of 20:1, mixed for about 1 hour and 30 minutes, and then filtered, washed, and dried to form silicon-based composite particles. The average particle size (D 50 ) was 5 μm and the pore size was 15 nm.

[0167] (3) Preparation of reserve negative electrode active material The silicon-based composite particles were placed in a hot zone of a CVD apparatus while maintaining an inert atmosphere by flowing Ar gas around the silicon-based composite particles. The methane was then blown into the hot zone at 920° C. using Ar as a carrier gas for 3 hours and 10 minutes. -1 The reaction was carried out at torr to form a preliminary negative electrode active material having an outer carbon layer (thickness: 30 nm) formed on the surface of the silicon-based composite particles and an inner carbon layer formed inside the pores.

[0168] (4) Manufacture of negative electrode active material The preliminary negative active material having the outer and inner carbon layers was subjected to an additional heat treatment (second heat treatment) at 950° C. for 3 hours to control the size and number of pores in the silicon-based composite particles, thereby producing a negative active material. 50 ) is 5 μm, and the BET specific surface area is about 7.5 m 2 / g.

[0169] The negative active material had a Li content of 2.1 wt%, and the total weight of the outer carbon layer and the inner carbon layer was 24.9 wt% based on 100 wt% of the negative active material. Specifically, the outer carbon layer was 3.2 wt% and the inner carbon layer was 21.4 wt% based on 100 wt% of the negative active material.

[0170] (Example 2-2) A negative active material was prepared in the same manner as in Example 2-1, except that the preliminary silicon-based composite particles were mixed in the etching solution for 2 hours.

[0171] (Example 2-3) A negative electrode active material was prepared in the same manner as in Example 2-1, except that the silicon-based composite particles were reacted with methane in a hot zone at 920° C. for 5 hours.

[0172] (Examples 2-4) A negative electrode active material was prepared in the same manner as in Example 2-1, except that the preliminary silicon-based composite particles were mixed in the etching solution for 3 hours, and then reacted with methane in a hot zone at 920° C. for 4 hours.

[0173] (Comparative Example 2-1) A negative electrode active material was prepared in the same manner as in Example 2-1, except that the preliminary silicon-based composite particles were not etched.

[0174] (Comparative Example 2-2) A negative electrode active material was prepared in the same manner as in Example 2-1, except that the preliminary silicon-based composite particles were mixed in the etching solution for 6 hours, and then reacted with methane in a hot zone at 920° C. for 1 hour.

[0175] (Comparative Example 2-3) A negative electrode active material was produced in the same manner as in Example 2-1, except that the silicon-based composite particles were reacted with methane in a hot zone at 970° C. for 5 hours.

[0176] [Table 3]

[0177] <Experimental Example 2: Evaluation of discharge capacity, initial efficiency, and life (capacity retention rate) characteristics> Negative electrodes and batteries were produced in the same manner as in Experimental Example 1 using the negative electrode active materials of the examples and comparative examples, respectively.

[0178] The produced battery was charged and discharged, and the discharge capacity, initial efficiency, and capacity retention rate were evaluated in the same manner as in Experimental Example 1. The results are shown in Table 4 below.

[0179] [Table 4]

[0180] The negative electrode active material according to the present invention is characterized in that it contains pores in silicon-based composite particles, an internal carbon layer in the pores, and an external carbon layer on the surface of the silicon-based composite particles, and the volume change of the negative electrode active material during charging and discharging of the battery is easily suppressed, the conductivity of the negative electrode active material is improved, and the life characteristics of the battery can be improved. Therefore, it can be confirmed that Examples 2-1 to 2-4 using the negative electrode active material according to the present invention show excellent discharge capacity, initial efficiency, and capacity retention rate.

[0181] In contrast, the negative active material used in Comparative Example 2-1 has a small BET specific surface area, and is unable to effectively suppress volumetric changes in the negative active material during charging and discharging, resulting in deterioration of the battery life characteristics. Also, the negative active materials used in Comparative Examples 2-2 and 2-3 have excessively large pore sizes or inadequate carbon layers, resulting in an excessively large BET specific surface area, and therefore increased side reactions between the electrolyte and the negative active material, resulting in deterioration of the battery life characteristics.

Claims

1. SiO x (0<x<2) and a silicon-based composite particle containing pores and an Mg compound or a Li compound; An outer carbon layer provided on the surface of the silicon-based composite particle; and An inner carbon layer provided inside the pores Including, BET specific surface area is 3m 2 / g to 15m 2 / g, The size of the pores is between 10 nm and 35 nm; When the silicon-based composite particles contain an Mg compound, the Mg element is contained in an amount of 0.5 wt % to 8 wt % based on a total of 100 wt % of the silicon-based composite particles; When the silicon-based composite particles contain a Li compound, the Li element is contained in an amount of 0.5 wt % to 8 wt % based on 100 wt % of the total weight of the silicon-based composite particles.

2. 2. The negative electrode active material according to claim 1, wherein the Mg element is contained in an amount of 0.8 to 4 wt % based on a total of 100 wt % of the silicon-based composite particles.

3. 2. The negative electrode active material according to claim 1, wherein the lithium element is contained in an amount of 0.5 to 4 wt % based on a total of 100 wt % of the silicon-based composite particles.

4. 2. The negative electrode active material of claim 1, wherein a total weight percentage of the outer carbon layer and the inner carbon layer is 5 to 40% by weight based on 100% by weight of the total negative electrode active material.

5. The negative active material of claim 1 , wherein the outer carbon layer is present in an amount of 1 wt % to 10 wt % based on a total weight of the negative active material (100 wt %).

6. The negative active material of claim 1 , wherein the inner carbon layer is included in an amount of 4 wt % to 35 wt % based on 100 wt % of the total weight of the negative active material.

7. The average particle size (D 50 2. The negative electrode active material according to claim 1, wherein the average particle diameter is 2 μm to 15 μm.

8. SiO x (0<x<2), forming silicon-based composite particles containing pores from preliminary silicon-based composite particles containing an Mg compound or an Li compound; disposing a carbonaceous precursor on the silicon-based composite particles and then performing a first heat treatment to form a preliminary negative electrode active material including an outer carbon layer and an inner carbon layer; and subjecting the preliminary negative electrode active material to a second heat treatment. The method for producing the negative electrode active material according to any one of claims 1 to 7, comprising:

9. The SiO x 9. The method for producing a negative electrode active material according to claim 8, wherein the step of forming silicon-based composite particles containing pores from preliminary silicon-based composite particles containing an Mg compound or an Li compound includes a step of etching the preliminary silicon-based composite particles using an acid or a base.

10. The method of claim 8, wherein the first heat treatment is performed at 600° C. to 1100° C.

11. The method of claim 8, wherein the second heat treatment is performed at a temperature of 600° C. to 1100° C.

12. A negative electrode comprising the negative electrode active material according to any one of claims 1 to 7.

13. A secondary battery comprising the negative electrode according to claim 12.

Citation Information

Patent Citations

  • Electrode active material for secondary battery

    JP2014026949A

  • Lithium ion secondary battery

    JP2016167352A

  • Negative electrode active material for lithium secondary battery and its manufacturing method

    JP2018523898A

  • Negative electrode active material for non-aqueous electrolyte secondary battery containing silicon oxide composite and method for producing same

    JP2021504918A

  • Negative electrode active material, preparing method of the same, negative electrode and lithium secondary battery including the same

    KR1020190104895A